2012
DOI: 10.1242/dev.073734
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal changes in actin and microtubules underlie the developing surface mechanical properties of sensory and supporting cells in the mouse cochlea

Abstract: SUMMARYCorrect patterning of the inner ear sensory epithelium is essential for the conversion of sound waves into auditory stimuli. Although much is known about the impact of the developing cytoskeleton on cellular growth and cell shape, considerably less is known about the role of cytoskeletal structures on cell surface mechanical properties. In this study, atomic force microscopy (AFM) was combined with fluorescence imaging to show that developing inner ear hair cells and supporting cells have different cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 72 publications
3
72
0
Order By: Relevance
“…Our results are in agreement with previous findings that in vitro HC regeneration after laser ablation of embryonic HCs decreased in a basal-apical gradient (Kelley et al, 1995). Both HCs and SCs continue to mature during the first postnatal weeks, with cytoskeletal, morphological and functional changes detected in cells from the basal turn 2-3 days before cells in the apex (Hallworth et al, 2000;Jensen-Smith et al, 2003;Legendre et al, 2008;Lelli et al, 2009;Szarama et al, 2012). Thus, cells in the apical turn are less mature, which might provide a permissive environment for HC regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with previous findings that in vitro HC regeneration after laser ablation of embryonic HCs decreased in a basal-apical gradient (Kelley et al, 1995). Both HCs and SCs continue to mature during the first postnatal weeks, with cytoskeletal, morphological and functional changes detected in cells from the basal turn 2-3 days before cells in the apex (Hallworth et al, 2000;Jensen-Smith et al, 2003;Legendre et al, 2008;Lelli et al, 2009;Szarama et al, 2012). Thus, cells in the apical turn are less mature, which might provide a permissive environment for HC regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…We have already shown that during this critical period, pillar and Deiters' cells undergo dramatic morphological and molecular changes (Johnen et al 2012). It has also been demonstrated that during these stages, microtubules progressively develop to reach the large number found at the adult stage (Tucker et al 1998;Szarama et al 2012). In the present paper, we report a huge increase in the labelling of pillar cells for all β-tubulin isotypes at P6, confirming these previous data.…”
Section: Deiters' Cellssupporting
confidence: 91%
“…, 2011) and the pillar cells of the inner ear, which offer mechanical support to the sensory hair cells (Tannenbaum and Slepecky, 1997; Szarama et al. , 2012).…”
Section: Resultsmentioning
confidence: 99%